Stromboli or Russian roulette tourism - Rémy Knafou (Via@)
Stromboli is one of the most active volcanoes on the planet; it has also become a tourist hotspot for just over half a century.The recent eruptive paroxysms of summer 2019 have spectacularly highlighted this paradoxical situation because, for the first time in its history, this paroxysm occurred during the tourist season. A quite happy combinations of circumstances made possible to avoid a balance which could have been catastrophic, but it also revealed the limits of the Aeolian tourism system which has partly built its international notoriety on the volcanic attraction.This article therefore questions the relationship between the unpredictability of a potentially fatal, but very exceptional risk, and the management of an intense tourist frequentation during the season, little or not informed about the reality of the risks.